Evaluasi Penerimaan Pajak Bumi dan Bangunan (PBB) Setelah Penetapan UU No. 28 Tahun 2009 Serta Kontribusinya Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Sragen Tahun 2010-2014 - Herdiana, Riska, Dra. Mujiyati, M.Si (2016)
According to the Law No. 28/2009 about Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) is one of the taxes administered by the regional government. Sragen government prepared for the transfer of land and building tax in 2013 and formally accepted the PBB-P2 delegated management of the central government per January 2014. The aim of this study is to determine the PBB-P2 acceptance after enactment of the Law No. 28/2009 and it's contribution to revenue (PAD). The object of this study is the Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah (DPPKAD) of Sragen. This research uses quantitative descriptive method to analyze the data. The data used in this study is secondary data from documentation, library research, and interviews with relevant parties. The results showed that the real action of accepting PBB-P2 in 2010-2014 in Sragen has reached the target. The growth rate of acceptance of the PBB-P2 after the promulgation of Law No.28/2009 decreased the precentage, it is because the target set by the government is greater than the target set by the central government. The level of effectiveness in the years 2010-2014 in the criteria of highly effective, because realizations have exceeded the target. As for the PBB-P2 contribution to the PAD before and after enactment Law No. 28/2009 decreased the percentages. Keywords: evaluation, pbb-p2, effectiveness, contributions